Management Practices of Filipino Nursing Deansas Curriculum and Instruction Leaders - Helen Abiera, Helen Abiera; Ancho, Inero (Princess of Naradhiwas University Journal, 2023)
Academic operation of nursing program is challenging. The deans who served as a program administrator were once working as nurses in the clinical setting or faculty members of nursing schools. Deans are expected to manage the nursing program and produce graduate nurses ready to practice the profession. This qualitative study which involved 19 participants was done to identify the common management practices and competencies of the deans as described by themselves, students, faculty members, and immediate supervisor utilizing a multicase study design. Curriculum and Instructional Leadership domain covered the common management practices of the functions and responsibilities of deans as stipulated by the Commission on Higher Education (CHED) Memorandum Order Number 15 series 2017. The results show that the dean as an instructional leader was engaged in curriculum and instructional development and evaluation with the involvement of faculty members and stakeholders. The deans were advancing change and innovation of instruction and assessment and promoting the use of digital resources.